A Feasibility Study on Cordierite-Based Products - Difuntorum, Lee Michael N.; Gabaon, Jennifer Frances M.; Paynor, Edgar Kevin P. (Diliman, Quezon City College of Engineering, 2002)
Every rational decision to make a new investment is preceded by an investigation of the project's feasibility. The study focused on the production of Cordierite-based refractory. Cordierite is a magnesium-alumina-silicate material used as refractories such as for furnace linings and as kiln furniture. Kiln furniture is primarily used for the production of any product that is fired in kilns or ovens. In the marketing study, the demand for kiln furniture was established as well as the supply Of Cordierite. The target market of the product was identified. The product would be sold to different industries, such as ceramic, glass and metal industries, utilizing kilns; hence, use refractory materials in producing their respective products. The competitor and industry analyses defined that an extensive marketing program would be needed to promote Cordierite-based refractories as a viable substitute to current refractories being used by the aforementioned industries. After determining the preliminary information requirements, such as the product, the market and materials information, from the marketing study, the technical aspect of the feasibility study was conducted. Production necessities, specifically equipment and machine requirements, manpower level and space needed for the manufacturing facility were identified. Finally, venture initiation cost was found out to be P97,039,874.73. It was ascertained that the project was technically feasible. In the financial study, the detailed cost analyses were presented as well as the cash projections to be incurred by project on a yearly basis. Various tests and indicators were performed to determine the project's ability to meet its projected financial obligations. The study showed the project?s internal rate of return at 47,384%, a net present value of P1,156,555,278, and a payback period of 1.69 months. The social profitability study was able to resolve that the project was socially attractive for the government and inevitably to the country in general, and to the manufacturing facility in particular. Benefits include taxes contributed to the government, employment, utilization of local materials, among others. The marketing, technical and financial viability of producing Cordierite-based refractories were conducted to attest that the project is feasible. Furthermore, the organizational structure and the socio-economic impact of putting up a project were studied. In accomplishing this, the overall feasibility of Cordierite-based refractories was established and this resulted to the underlying conclusion that the conception of CORDIERAMICS PHILS., INC is without doubt, feasible.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Ceramic industries; Refractory materials; Cordierite; Participatory monitoring and evaluation (Project management)